Autoimmune diseases of the skin pathogenesis, diagnosis, management - Hertl, Michael (Springer Vienna, 2011)
Autoimmune disorders of the skin remain an enigma for many clinicians and scientists not familiar with these mostly severe and chronic diseases. The book provides an overview and the latest information on the broad spectrum of cutaneous autoimmune disorders for clinicians, scientists and practitioners in dermatology, medicine, rheumatology, ENT, pediatrics and ophthalmology. The book is unique since it presents the state-of-the-art knowledge on pathophysiology, clinical diagnosis and management of these disorders provided by the world experts in the field. The primary intention is to broaden the understanding of the pathophysiology of cutaneous autoimmune disorders and to provide a practical guide to how to identify and handle these conditions. The book is illustrated with many tables, illustrative figures and clinical color photographs. The third edition has been thoroughly updated and extended by chapters on paraneoplastic cutaneous syndromes, atopic dermatitis and autoimmunity and Skin manifestations of rheumatic diseases.